All-Inside PCL Reconstruction - Therrien, Erik; Pareek, Ayoosh; Song, Bryant M.; Wilbur, Ryan R.; Stuart, Michael J.; Levy, Bruce A. (The Journal of Knee Surgery, 2021)
Many different techniques with multiple graft types have been described for the reconstruction of the injured posterior cruciate ligament (PCL); autograft versus allograft, single- versus double-bundle, open inlay versus arthroscopic inlay versus arthroscopic transtibial, and recently described the arthroscopic “all-inside” socket technique. Reported clinical outcomes have demonstrated no significant difference in any of these PCL reconstruction techniques, likely because of the heterogeneity in injury characteristics and patient population. The ideal surgical technique should be safe, simple, and reproducible while allowing treatment of concomitant knee injuries resulting and return to function.
Keywords: posterior cruciate ligament; PCL; PCL reconstruction; all-inside PCL reconstruction